Encapsulated Phage Cocktail: The Destined Environmental Biocontrol Agent For Pathogenic Leptospira - Fang, Kokxin; Md Nor, Norefrina Shafinaz (Malaysian Applied Biology, 2024)
Leptospirosis is one of the often-neglected fatal zoonotic diseases endemic to most developing countries. The disease transmits mostly through contact of rodent urine contaminated with pathogenic Leptospira in the environment. This review discusses the need for environmental bioremediation of these pathogens and the reasons phage could very well be employed for that purpose. With a few modifications like encapsulation and cocktail formulation, the functionality and stability of phage as the natural predator could easily be heightened. Host specificity, ability to auto-dose and co-evolve along its hosts, effectiveness against biofilms and independence of its production are some of the promising features of a phage. Here we also highlight the interactions and interference among phages in a cocktail, transduction probability, and hypothetic usage of phage lysin in biocontrolling pathogenic Leptospira.